Work behavior analysis using do it method on the daily check officers at the locomotive depot of operation area VI Yogyakarta, Indonesian railway company - Hariyono, Widodo; Ramadhan, R. Mulya Rizkitiar (Universitas Ahmad Dahlan, 2022)
Background: One of the efforts to reduce accidents is to use the Do It method. Work accidents caused by incorrect work behavior. One of the theories used for the ABC theory uses the Do It method to perform maintenance. The purpose of this study is to determine the behavior of workers in the Daily Check section at the Locomotive Depo PT. Kereta Api Indonesia (Persero) Operation Area VI Yogyakarta using the Do It method. Method: This type of research is qualitative research. Subjects in the study were 5 people consisting of 4 officers of the Daily Check section and 1 leader of the Quality Control Section. Data collection is done by observation, reviewing documents, and interviews. Results: The results of the study revealed that the status of workers' behavior in the Daily Check section officer in the category behaved safely. Judging from the predetermined and observed behavioral targets, the safety briefing activities have a percentage of 90% behavioral status, 62,5% percentage of Personal Protective Equipment (PPE) use behavior, and 94,2% percentage of compliance procedures. Conclusion: The behavior status of workers in the Daily Check section officer behaves safely. Behavioral targets and observations were carried out namely safety briefing activities, PPE use behavior, and compliance with work procedures.